2013
DOI: 10.1017/jfm.2013.83
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent wake past a three-dimensional blunt body. Part 1. Global modes and bi-stability

Abstract: The flow around the three-dimensional blunt geometry presented in the work of Ahmed, Ramm & Faitin (Tech. Rep., 1984) is investigated experimentally at $\mathit{Re}= {U}_{0} H/ \nu = 9. 2\times 1{0}^{4} $ (where ${U}_{0} $ is free-stream velocity, $H$ the height of the body and $\nu $ viscosity). The very large recirculation on the base responsible for the dominant part of the drag is characterized. The analyses of the coherent dynamics of the wake reveal the presence of two very distinctive time scales. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

68
247
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(317 citation statements)
references
References 36 publications
68
247
2
Order By: Relevance
“…In the spectrum of the angular component, a power-law with an exponent close to -2 is obtained at very low frequencies (VLF). This is analogous to the results of Grandemange et al (2013), and consistent with Brownian dynamics (Brown & Ahlers 2006). Hence the VLF oscillation is a random rotation of the CoP in the azimuthal direction around the axis of the body.…”
Section: On the Symmetry Of The Flowsupporting
confidence: 87%
“…In the spectrum of the angular component, a power-law with an exponent close to -2 is obtained at very low frequencies (VLF). This is analogous to the results of Grandemange et al (2013), and consistent with Brownian dynamics (Brown & Ahlers 2006). Hence the VLF oscillation is a random rotation of the CoP in the azimuthal direction around the axis of the body.…”
Section: On the Symmetry Of The Flowsupporting
confidence: 87%
“…Monkewitz (1988) conducted a linear stability analysis for a family of axisymmetric wake (parallel flow) profiles: he showed that this asymmetric mode is absolutely unstable, and in agreement with experimental observation by Taneda (1978), he noted that it is most clearly observed somewhat downstream of the body. Grandemange et al (2013) show that these characteristics are consistent with those of a wake from a threedimensional body of rectilinear geometry. Ho & Huerre (1984) have identified the boundarylayer momentum thickness, θ, as the appropriate length scale.…”
Section: Introductionsupporting
confidence: 71%
“…Such low-frequency variations result in the axial symmetry being achieved only by very long-term averaging. An analogous instability has been observed in the wake behind spheres 9 as well as rectilinear bodies (e.g., Ahmed bodies), 10 whereby in the latter case it occurs as an irregular shift of the recirculation bubble between two preferred anti-symmetric states. Furthermore, this phenomenon shows similarity with the precession motion experienced by the stagnation point in the wake of turbulent annular jets, 11 featuring a comparable characteristic frequency (St D ≈ 0.0025, D being the jet diameter).…”
Section: Introductionsupporting
confidence: 53%
“…The existence of such a backflow low-frequency unsteadiness has previously been linked to the persistence in the turbulent regime of the symmetry-breaking mode, 10,11 with the prescribed symmetry plane continuously changing its orientation in view of its sensitivity to external perturbations. 12,13 Asymmetries in the near-wake flows of axisymmetric bodies have been documented in the literature for subsonic conditions [14][15][16] as well as in the transonic 17 and supersonic regime 18 and are mainly ascribed to boundary condition effects such as misalignments between wind-tunnel model and free-stream flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation